2009
DOI: 10.1017/s0021855309990076
|View full text |Cite
|
Sign up to set email alerts
|

Nigeria's Land Use Act: An Anti-Thesis to Environmental Justice

Abstract: Nigeria's Land Use Act, promulgated in 1978, is perhaps the most controversial legislation in the country. The Act, originally promulgated as a decree and annexed to the country's constitution, was ostensibly made to nationalize landholding in the country. However, the peculiar impact of the Act on the inhabitants of the Niger Delta region that hosts upstream activities of the oil industry has led to assertions that the Act was made specifically to deprive those inhabitants of the right to participate actively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Legally, Abioye v. Yakubu established that the law removed both radical title and control from families, community heads, and chiefs, vesting it in the governors of states "for the use and benefit of all Nigerians" (Ako, 2009). Studies of the decree have reached divergent conclusions; Francis (1984) found that elites had used the law to increase their influence in local politics, while Berry (1985) concluded land tenure in her Yoruba sample was largely unaffected.…”
Section: Nigeriamentioning
confidence: 99%
See 1 more Smart Citation
“…Legally, Abioye v. Yakubu established that the law removed both radical title and control from families, community heads, and chiefs, vesting it in the governors of states "for the use and benefit of all Nigerians" (Ako, 2009). Studies of the decree have reached divergent conclusions; Francis (1984) found that elites had used the law to increase their influence in local politics, while Berry (1985) concluded land tenure in her Yoruba sample was largely unaffected.…”
Section: Nigeriamentioning
confidence: 99%
“…Williams (1992) showed that most land transactions in Oyo state continued to operate outside state authority, and that the decree was largely unacknowledged. Ako (2009) argues that the act has led people of the Niger Delta to lose land, rights to compensation for damages done by oil companies, and effective means of conflict resolution. In 2009, President Yar'Adua inaugurated a Presidential Committee chaired by Akin Mabogunje as a forerunner to a National Land Commission.…”
Section: Nigeriamentioning
confidence: 99%
“…The Act heralded policies such as the power of the Governor to declare territory within the state urban or rural and decide what happens in their state's land (Land Use Act, 1978;Ako, 2009). Another of such policy is that which holds that urban land is meant for housing and other urban industrial use.…”
Section: The Land Use Act 1978mentioning
confidence: 99%
“…Simply put, the misrecognition of the host-communities aff ects their participation in the industry they host. 48 As Ostrom noted, in complex situations such as Nigeria's oil industry, the solution does not lie simply in ownership arrangements but governance solutions that provide for participation in collective decisions and make confl ict resolution available for involved actors. 49 Consequently, it is suggested that the legal framework regulating Nigeria's oil industry laws, which perpetuates the 'asymmetrical relationship' between the industry and the host-communities, must be reviewed.…”
Section: Conclusion: Recommendations For Peace In the Crude-oil Eramentioning
confidence: 99%